An unusual new genus and species of centrotine treehopper (Hemiptera: Membracidae: Centrotinae) from Nicaragua - Morris, Brendan O.; Dietrich, Christopher H. (Zootaxa, 2020)
A new genus and species of treehopper (Membracidae: Centrotinae) from Nicaragua, Kaikaia gaga, is described and illustrated. Kaikaia is particularly notable in having an assemblage of features more characteristic of the Old World centrotine tribe Beaufortianini than currently recognized New World centrotine tribes. Kaikaia lacks cucullate setae of the mesothoracic femora, which are present in the Boocerini and to some extent, the Platycentrini. The new genus also has an additional m-cu crossvein in the forewing, as well as a frontoclypeal shape and overall appearance similar to Platycentrus Stål. Nevertheless, Kaikaia differs from Platycentrus in its narrow, straight shape of the second valvulae, which bear several prominently raised dorsal teeth and an acute projection along the dorsal margin that resemble those of some members of Nessorhinini.